Emerging role of cell polarity proteins in breast cancer progression and metastasis - Chatterjee, Sudipa June (Dove Medical Press, 2014)
Breast cancer is a heterogeneous group of diseases that frequently exhibits loss of growth control, and disrupted tissue organization and differentiation. Several recent studies indicate that apical–basal polarity provides a tumor-suppressive function, and that disrupting polarity proteins affects many stages of breast cancer progression from initiation through metastasis. In this review we highlight some of the recent advances in our understanding of the molecular mechanisms by which loss of apical–basal polarity deregulates apoptosis, proliferation, and promotes invasion and metastasis in breast cancer.